PERBANDINGAN HASIL BELAJAR MATERI RELASI DAN FUNGSI MENGGUNAKAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER DAN THINK PAIR SHARE - Salajang, Santje; Wenas, John; Singal, Fraulein Carol (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. This research was aimed to know the differences in student learning outcomes on relation and function lesson among a group of students whom using the numbered head together (NHT) model, think pair share (TPS) model, and conventional models of learning. This research was conducted at SMP Negeri 1 Remboken in the odd semester during the 2019/2020 academic year. Subjects in the research were students of class VIII D as the control class, class VIII C as the 1st experimental class and class VIII E as the 2nd experimental class. The results of data analysis, shown that the average score in the 1st experimental class was 79.81 and in the 2nd experimental class was 79.00, while the average score in the control class was 69.09. The results of hypothesis test found that Fcount=3.637, and Ftable=3,150.  Fcount>Ftable, then reject H0, meaning that there were significant differences in the average learning outcomes between students who use the NHT, TPS, and conventional model on relation and function. Further test result obtained are the average student learning outcomes using the NHT and TPS models of learning significantly different from the average learning outcomes of  students  who use conventional  models of learning. Keywords: Conventional, NHT, TPS